(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2020)
Smallholder potato producers in Jeldu district produce potato for both home consumption and market. Adoption of improved varieties is suggested to improve and diversify farmers’ household income. This study intents to identify factors determining adoption and intensity of adoption of improved potato varieties in Jeldu district of West Shewa zone, Oromia region, Ethiopia. Both primary and secondary data were used. The primary data were collected from 140 sample households’ selected using two-stage random sampling techniques. Descriptive statics and double hurdle econometric model were used to analyze the data. Results indicate that sex of the household head, access to extension services, livestock ownership and farmers’ perception about the technology positively and significantly determined adoption of improved varieties in the district. In contrast, distance from the nearest market affected adoption of improved potato varieties negatively and significantly. Intensity of adoption is measured by the area of land allocated for improved potato varieties by farmers. The truncated result identified improved varieties yield perception, family size, livestock ownership and membership to agricultural cooperative influenced intensity of improved potato varieties adoption positively and significantly. Strengthening extension services to enhance farmers’ awareness about improved potato varieties infrastructure development, family planning, asset ownership and facilitating membership to cooperatives are recommended. Int. J. Agril. Res. Innov. Tech. 9(2): 15-22, December 2019